Pilomatrixoma of the right cheek in a young girl - Amjad Tallaa A Tallaa; Misheal Madni; Laila Salah Seada; Adel Ahmed Alfayez; Mohammed Fahad Alateeq (Elsevier, 2018)
Objective: We report a case of pilomatrixoma of the right cheek in a healthy 4 years old girl. Method: Case report and review of the English language literature (using PubMed, Ovid and Proquest databases). Results: Case of right cheek pilomatrixoma occurred in a young girl to be reported in the English language literature. Conclusion: Pilomatrixoma is a cutaneous neoplasm that is one of most common causes of superficial head and neck masses in children. Although the presurgical diagnosis may be difficult in some cases, pilomatrixoma must be kept in the differential of superficial head and neck masses in children. The present case highlights the importance of considering pilomatrixoma in the clinical and pathologic differential diagnosis of dermal or subcutaneous nodule even in locations other than head and neck region. Surgical excision is almost always curative.